ヌルメ イケ ノ ビリョウ キンゾク ノ エンチョク ブンプ - 佐野, 方昴; サノ, マサタカ; 中井, 信之; ナカイ, ノブユキ; 鳥居, 鉄也; トリイ, テツヤ; SANO, Masataka; NAKAI, Nobuyuki; TORII, Tetsuya (国立極地研究所, 1977)
P(論文) 南極ラングホブデ地区,ぬるめ池の微量金属の垂直分布を測定した.同池の池水は,大きく2層に分けられ,下層は強い還元状態であり,硫化水素が存在した.微量金属は,表面水では比較的高い濃度であり,融雪水の影響を受けたものと推定された.また,中間層ではMnの極大が見られ,下層ではFe, Mnが高濃度に存在し,2層構造に強く支配されていることがうかがわれた.湖底堆積物中の微量金属は,表面から約80cmの深さまでほとんど変化せず,この間の微量金属の供給源物質および堆積環境の類似性が推定された. The concentration of some trace metals (Fe, Mn, Cu, Zn, Pb, Cd) in Lake Nurume was measured vertically. The concentration of trace metals in surface water decreases with increasing depth to the intermediate water layer. This fact may be ascribed to snow melt added to the surface water. The water layer, which retains reduced environment throughout the year, is found at a depth deeper than 10 m in the pond. This structure is thought to be an important factor of the vertical distribution of trace metals. The Mn concentration maximum was found at a boundary layer between oxidative and reductive layers. In the reductive layer, Fe and Mn are more abundant than in the oxidative layer, because of the increased solubility. The concentration profile of trace metals in the bottom sediment did not show any significant change down to a depth of 80 cm below the water-sediment interface. The fact may suggest that the material supplied from the same source was deposited in a stable environment. departmental bulletin paper